Perubahan Strategi Teroris Selama Masa Pandemi Covid-19 - Beny A Tatara; Wahyu Sekti Retnaningsih (Yayasan Literasi Sains Indonesia, 2022)
The Covid-19 pandemic has changed all aspects of people's social life. This is exploited by terrorists by changing their strategy by adapting to new patterns of community life with the aim of reaffirming their existence. The purpose of this study is to analyze changes in terrorist strategies during the Covid-19 pandemic. This study uses a qualitative method with a literature study approach. The results of the study show that during the Covid-19 pandemic, terrorists changed their strategy by using the internet more in their activities.. The internet has been used as a medium for spreading radicalism and terrorism. Terrorist groups use the internet for propaganda, recruitment and financing. Propaganda with internet media is carried out by terrorist groups in two ways, namely Official propaganda and Unofficial propaganda which is carried out through five online media platforms namely Twitter, Facebook, Tumblr, YouTube and the world wide web. Propaganda activities carried out are used as the first step in the recruitment process which will then be followed by a personal approach to potential terrorists. Apart from being a media for propaganda and recruitment, the internet is also used as a medium for funding such as cryptocurrencies, virtual currency, crowdfunding, fundraising, and social media networks which make traces of transactions difficult to detect and trace by security forces.